PENGARUH KUALITAS PELAYANAN DAN REPUTASI PERUSAHAAN TERHADAP KEPUASAN KONSUMEN DENGAN KEPERCAYAAN SEBAGAI VARIABEL MODERASI - Didik Prayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The goal of this research is to analyze the significance of the service quality influence, reputation and trust to consumer satisfaction of Jayapura Motor repair shop in Jatipuro Karanganyar. To analyze whether the trust moderating services quality influence and company reputation to consumer satisfaction at Jayapura Motor repair shop in Jatipuro Karanganyar. The result of this research conclude there is a significance influence from service quality, company reputation and trust to consumer satisfaction at Jayapura Motor repair shop in Jatipuro Karanganyar. Trust isn’t moderating the service quality influence to consumer satisfaction at Jayapura Motor repair shop in Jatipuro Karanganyar. Trust moderating the influence of company reputation to consumer satisfaction at Jayapura Motor repair shop in Jatipuro Karanganyar. Keywords: Quality Services, Company Reputation, Trust and Consumer Satisfaction